Implementation of Teacher Development Program for Integrating Climate Change Education: Natural Sciences Teachers View - Kayode OLAWUMI; Mzuyanda Percival MAVUSO; Xolani KHALO; Babalwa KAFU-QUVANE; Busiswa MZILIKAZI (International Journal of Environmental, Sustainability, and Social Science, 2023)
The devastating effect of climate change (CC) on the environment all over the world has been a worrisome phenomenon. The effort by the government and other stakeholders at integrating climate change education (CCE) into the school curriculum in South Africa has not yielded the desired result because of the lack of teacher professional training programs for teaching CCE in the classroom. Using the pedagogical content knowledge (PCK) theory as lenses, this qualitative study investigated the implementation of the in-service teacher development programs and their role in enhancing the integration of CCE in Natural Sciences lessons. Five secondary schools out of twenty schools that participated in the in-service teacher training program conducted by one higher education institution (HEI) were purposely selected. Data for this study were generated through one-on-one semi-structured interviews conducted with four participating Natural Sciences teachers at the selected schools. It emerged from the data that the implementation of in-service teacher development programs helped Natural Sciences teachers to integrate CCE into their lessons. The data also revealed that Natural Sciences teachers’ content and pedagogical content knowledge on CC was lacking thus they were not adequately integrating CCE in their lessons. The study concludes that the teacher training programs are responsible for teacher improved pedagogical practice of Natural Sciences teachers in the classroom and the integration of CCE. The paper, therefore, recommends that teacher professional development programs on CCE for Natural Sciences teachers be organized on a continuous basis.